Surface fertilisation and organic matter delivery enhanced carbonate dissolution in the western South Atlantic - Suárez-Ibarra, Jaime Y.; Freire, Tiago M.; Frozza, Cristiane F.; Pinho, Tainã M. L.; Petró, Sandro M.; Dias, Bruna B.; Chalk, Thomas B.; Chaabane, Sonia; Srivastava, Medhavi; Costa, Karen B.; Toledo, Felipe A. L.; de Garidel-Thoron, Thibault; et al. (Frontiers in Ecology and Evolution, 2023)
The last glacial inception was characterised by rapid changes in temperature, atmospheric pCO2, and changes in the water mass geometry of the major ocean basins. Although several climatic feedback mechanisms have been proposed to explain the glacial/interglacial cycles witnessed in the Quaternary, the exact mechanistic responses of these processes are still under constrained. In this study we use proxies including planktonic foraminifera compositional assemblages and oxygen stable isotopes to reconstruct past changes in sea surface productivity, stratification, and carbonate dissolution. We use core SIS-249 (2,091 mbsl, western South Atlantic 30°S 47°W), spanning 30–110 thousand years ago (ka), and currently bathed by modern Northern Component Water. We test existing hypotheses suggesting that the orbital obliquity cycle modulates the biological pump in the study area. Spectral analysis run on our synthesised productivity proxies recognises a ~43 kyr-cycle, related to the obliquity cycle. We propose that the enhanced productivity is produced by two mechanisms: i) the glacial upwelling of subsurface nutrient-rich waters and, ii) the continental (wind-driven dust and riverine outflows) fertilisation of the photic zone, with the latter process being obliquity-paced. We also suggest that not only the increased organic matter export but also a change in its bioavailability (from refractory to labile) led to calcium carbonate dissolution, as the degradation of the more soluble organic matter decreased the pH of the glacial bottom water, partially dissolving the calcium carbonate. Although our correlation analyses show a strong benthic-pelagic coupling through the relation between the enhanced biological pump and carbonate dissolution (ρ<0.05, r=0.80), we cannot reject the potential of corrosive Southern Component Water bathing the site during the glacial. Finally, we highlight that these processes are not mutually exclusive and that both can be modulated by the obliquity cycle.